Evaluating the Potential of Microorganisms in Bioremediation of Lead Polluted Soil - Atikpo, E.; Ihimekpen, N. I. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2020)
This study evaluated and compared the abilities of indigenous Bacillus sp. and Micrococcus sp. for treating lead polluted soil.  The organisms were inoculated into the contaminated soil samples prepared with the optimum values of screened determinant factors and experimented on 8, 16, 24, 32, 40, 48, and 56 days respectively for lead ion residual concentration using Atomic Absorption Spectrophotometer. Bacillus sp. showed greater remediation strength than Micrococcus sp. The results show that Bacillus sp. attenuated the Pb initial concentration from 150.74 mg/kg to control level in 40 days while Micrococcus sp. achieved that in 48 days. The 56th day residual concentrations and removal efficiencies were 81.43 mg/kg and 46% for Bacillus sp., and 86.91 mg/kg and 42.34% for Micrococcus sp. The removal rate was higher for Bacillus sp. (-0.0715 d-1) than for Micrococcus sp. (-0.0744d-1); and the remediation process was transport controlled. This information will be useful for remediation programs; and it will serve as a reference material for future research.